Exploration of tourist behavior in supporting sustainable tourism: A case study in Ubud village, Gianyar regency - Sitohang, Lidya Lestari; Nisma, Septia Illa; Wicaksono, Krisna Jadug Setyo; Wibawa, Karensa Puja Restu (Jurnal Pariwisata Pesona, 2025)
Ubud is a world-class tourist destination renowned for its unique blend of natural beauty, cultural richness, and spirituality rooted in the Tri Hita Karana philosophy. The accelerated growth of tourism necessitates a sustainable development approach to ensure a balance between economic growth and environmental and socio-cultural preservation. The objective of this study is to analyze tourist behavior in support of sustainable tourism practices in Bali, with a particular focus on Ubud. The present study was conducted using a quantitative descriptive method, with the Rapid Assessment Procedure (RAP) being applied. The sampling technique employed was that of accidental sampling. The data collection process entailed the administration of Likert-scale questionnaires, the conduction of in-depth interviews, and direct observations at tourist sites. The analysis focused on tourists' perceptions of their behavior in relation to supporting sustainable tourism involving environmental, sociocultural, and educational aspects. The results of this study suggest that tourists actively support sustainability based on their moral values, which involve allocentric, psychocentric, and midcentric behaviors. This research contributes to achieving the Sustainable Development Goals (SDGs) of building resilient cities (Goal 11) and ensuring the sustainability of terrestrial ecosystems (Goal 15).